Analysis of the Application of Vitamin B1 on the Response of Salinity Stress Resistance in Several Varieties of Rice (Oryza Sativa L.) - Tri Ratnasari; Tri Handoyo; Parawita Dewanti; Didik Pudji Restanto (Jurnal Penelitian Pendidikan IPA, 2024)
One of the most common stresses in rice cultivation is salinity. Rice plants stressed by salinity exhibit changes such as yellowing leaves, drying tips, and chlorosis. The efforts made by the government and farmers so far include implementing cultivation scheduling techniques, planting patterns, and using stress-resistant varieties, as well as improving soil to increase water-holding capacity through lime application. Each of these efforts comes with its own risks. Another approach to enhance the growth and yield of rice plants is the application of vitamins. Providing vitamins can stimulate the growth of plant organs, as they play a crucial role in the growth process by acting as catalysts for metabolism. Research has indicated that vitamin B1 can significantly promote plant growth under stressful conditions. This study aims to investigate the positive effects of various concentrations of vitamin B1 on the growth and yield of rice plants while also reducing salinity stress. The method used involved planting three varieties of rice—IR-46, Inpari-32, and Pokkali—in planting buckets using the TABELA system. Vitamin B1 was applied at concentrations of 0, 5, and 10 mM during the peak vegetative phase, with salinity stress of 6 dS/m introduced one day after vitamin application. The plants were maintained under salinity stress conditions until harvest, during which morphological and phytochemical analyses were conducted. Morphological analysis included measurements of plant height, number of tillers, number of productive tillers, number of grains per panicle, and percentage of healthy grains. Biochemical parameters measured included total chlorophyll and electrolyte leakage analysis. The results indicate that vitamin B1 can effectively reduce stress in plants affected by salinity.